Traditional Insurance for Male Aged in two Igbo Communities - A. A., Apeh; A.C., Ugwu (Journal of Home Economics Research, 2024)
This study focused on traditional insurance for the aged as embedded in the Enugu Ezike and Obukpa traditions. Specifically, it determined the mechanisms of traditional insurance and the ways they have influenced the aged. The study was a survey. The population was made up of males aged 65 and above. Interview schedule was used for data collection. Data collected were organised and discussed based on the specific purposes of the study. By tradition, those making use of lineage lands take certain quantities of the economic resource and money to the Okpara as tribute and for his upkeep. The aggregate of this contribution is a premium which serves as social support for elder. The findings reveal that most of the economic trees which used to form part of the livelihood of the aged had fallen due to development activities. The study recommends among others that various tiers of governments in Nigeria should provide necessary allowance to support the aged.